The Role of Paternal Parenting and Co-parenting Quality in Children’s Academic Self-Efficacy - Kara, Demet; Sümer, Nebi (Frontiers in Psychology, 2022)
described as the degree of consistency between paternal and maternal parenting behaviors on children’s academic self-efficacy. The power of both pancultural parenting behaviors (i.e., emotional warmth and rejection) and specific parenting controlling behaviors that are relatively common in Turkish culture (i.e., intrusion and guilt induction) in predicting academic self-efficacy was tested. A total of 1931 children completed the measures of parenting behaviors and academic self-efficacy on math and literature courses in their school. Overall, girls reported higher levels of literature self-efficacy whereas boys reported higher levels of math self-efficacy. Compared to boys, girls perceived higher levels of positive parenting behaviors from both their fathers and mothers. The results of the regression analyses showed that whereas father warmth had stronger effects on boys’ math self-efficacy, mother warmth had stronger effects on girls’ literature self-efficacy. Examination of the effects of coparenting quality demonstrated that children with positively consistent parents (i.e., both parents having high positive and low negative parenting behaviors) reported the highest levels of academic self-efficacy, whereas those having negatively consistent parents had the lowest level of academic self-efficacy. Analyses on inconsistent coparenting, however, yielded compensatory effects, which were similar to positively consistent parents and the deterioration effects, which were similar to the negatively consistent parents depending on the gender of parent and child, the domain of parenting behavior and academic efficacy. This study contributed to the current literature by showing the unique role of fathers over and beyond mothers and confirmed the importance of positive parenting and parenting consistency in promoting children’s academic efficacy. Cultural and practical implications of the findings were discussed.